Möbius Syndrome - Singham, Janakie (Thieme Medical Publishers, 2004)
Möbius syndrome is classically defined as combined congenital bilateral facial and abducens nerve palsies, although it may also be associated with a myriad of other craniofacial, musculoskeletal, cardiothoracic, endocrinologic, and developmental disorders. The problem that most patients complain about, however, is the inability to smile and close their lips while eating. Although the etiology of this syndrome is still unknown, scientific support has been growing for the hypothesis that it is due to an embryological disruption of subclavian artery development. The treatment of choice for facial reanimation in these patients is a neurovascular free muscle transfer, ideally using the gracilis muscle with direct repair of the gracilis muscle's motor nerve to the masseteric branch of the trigeminal nerve. If the masseteric nerve is unavailable, a partial hypoglossal or accessory nerve may be used. These operations, enhanced by the effects of cerebral plasticity, may allow Möbius patients to reach their goals of satisfactory spontaneous smiles.